The Asymptotic Behavior of a Stochastic Predator-Prey System with Holling II Functional Response - Zhenwen Liu; Ningzhong Shi; Daqing Jiang; Chunyan Ji (Abstract and Applied Analysis)
We discuss a stochastic predator-prey system with Holling II functional response. First, we show that this system has a unique positive solution as this is essential in any population dynamics model. Then, we deduce the conditions that there is a stationary distribution of the system, which implies that the system is permanent. At last, we give the conditions for the system that is going to be extinct.